Tingkat Pemahaman Aseptor KB tentang Penggunaan Alat Kontrasepsi Hormonal - Usman, Reni Devianti; Nurfantri, Nurfantri; Indrayana, Maman (Poltekkes Kemenkes Kendari, 2017)
The results of interviews conducted on mothers of hormonal contraceptive users in Lapulu Village working area of Abeli Care Center that they do not know what hormonal contraceptives are and do not know about the contraceptive methods they use in terms of Hormonal Contraceptives, Hormonal Contraceptive Advantages and Disadvantages, Indications and Contraindications of hormonal contraceptives. All they know is just how to delay pregnancy so that the distance of pregnancy is not too close to the low cost. This goal is to obtain a general overview of Family Planning Acceptance Knowledge about the use of hormonal contraceptives in Lapulu Village, Abeli Health Centre, Kendari. This type of research is a descriptive study with a sample of 49 people. The results of this study obtained respondents knowledge about the benefits of hormonal contraceptives obtained results as many as 23 people (46.94%) knowledge while knowledge is less than 26 people (53.06%) while respondents' knowledge of hormonal contraceptive side effects was 16 people (32.65%) knowledge is good while knowledge is less than 33 people (67.35%).